Computable Models - turner, raymond (Springer London : Imprint: Springer, 2009)
Computable models pervade present day science and engineering and are implicit in the specification of software systems. Raymond Turner first provides a logical framework for specification and the design of specification languages, then uses this framework to introduce and study computable models. In doing so he presents the first systematic attempt to provide computable models with a logical foundation. Computable models have wide-ranging applications from programming language semantics and the definition of specification languages, through to knowledge representation languages and formalisms for natural language semantics. They are also implicit in the computer modelling employed in many areas of science and engineering. This detailed investigation into the logical foundations of specification and its application to the construction of computable models should be of interest to a wide range of researchers including graduate students in mathematical logic and computer science.